2013
DOI: 10.1038/modpathol.2012.153
|View full text |Cite
|
Sign up to set email alerts
|

Loss of expression of SDHA predicts SDHA mutations in gastrointestinal stromal tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are usually driven by mutations in KIT or PDGFRA, although 15% of GISTs in adults and 490% in children lack such mutations. The majority of gastric KIT/PDGFRA wild-type GISTs show distinctive morphological and clinical features and loss of expression of succinate dehydrogenase (SDH) B. Only a small subset of SDHB-deficient GISTs carries loss-of-function mutations in SDHB, SDHC, or SDHD. Because of the complexity of its locus (15 exons) and the presence of three pseudogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 34 publications
(53 reference statements)
5
99
1
3
Order By: Relevance
“…In addition, in an Italian patient the same p.Arg31X was described recently 9 Also, Nannini et al, and Wagner et al, identified the SDHA p.Arg31X mutation (among others) in wild-type and SDHdeficient GISTs, respectively. 25,26 The frequency of SDHA mutations within the SDH-deficient GISTs (36%) of Wagner et al, is slightly higher, but in accordance with our frequency of SDHA-mutated GISTs that show a negative staining of SDHB (25%).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, in an Italian patient the same p.Arg31X was described recently 9 Also, Nannini et al, and Wagner et al, identified the SDHA p.Arg31X mutation (among others) in wild-type and SDHdeficient GISTs, respectively. 25,26 The frequency of SDHA mutations within the SDH-deficient GISTs (36%) of Wagner et al, is slightly higher, but in accordance with our frequency of SDHA-mutated GISTs that show a negative staining of SDHB (25%).…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies of SDH-deficient paragangliomas and GISTs have demonstrated that only tumors with SDHA mutations show negative SDHA immunohistochemistry (in addition to SDHB). [32][33][34] As expected, there was no abnormality of the SDHB gene detected by next-generation sequencing in this case. Unfortunately, SDHA was not included in the targeted sequencing panel, and therefore, the presence of an inactivating SDHA mutation could not be confirmed.…”
Section: Discussionmentioning
confidence: 61%
“…The absence of immunostaining for SDHA, as well as SDHB, is helpful in identifying GISTs with possible SDH gene mutations. 58,58,[62][63][64][65][66] Approximately 50% of wild-type GISTs demonstrate high expression of IGF1R. 67 In SDH-deficient GISTs, upregulation of IGF1 and IGF2 may activate IGF1R in an autocrine manner (Figure 3b), resulting in signaling through both the MAP kinase and PI3 kinase/AKT pathways.…”
Section: Sdh-deficient Gistsmentioning
confidence: 99%